Time-resolved structure-function coupling in brain networks - Zhen-Qi Liu; Bertha Vázquez-Rodríguez; R. Nathan Spreng; Boris C. Bernhardt; Richard F. Betzel; Bratislav Misic (Communications Biology, 2022)
Temporal unwrapping analysis of diffusion weighted MRI connectivity and functional MRI scans reveals that the coupling between structure and function in the human brain is regionally heterogeneous and provides a framework to evaluate these relationships from a dynamic perspective.